(untitled) (Asian Journal of Ethnobiology, 2020)
Abstract. Kurniawan A, Pramono DY, Indrayati A, Hermanto, Triswiyana I. 2020. Short communication: Differences in local perceptions of Osteochilus spilurus (Cyprinidae: Labeoninae) from several islands in Indonesia. Asian J Ethnobiol 3: 79-84. Osteochilus spilurus is native freshwater fish on the islands of Sundaland, Indonesia. No study has reported this fish utilization other than in the Belitung Islands, so another local perception of the Indonesian island needs to be investigated. Local recreational fishing in Palangkaraya, Pontianak, and Pekanbaru and fishers in Palangkaraya, Eastern and western of Belitung, Southern and Central Bangka, and North Lampung were the sources of local knowledge. We obtained data using a Facebook app survey to see local recreational fishers’ awareness, interviews with one fisherman in each region, and a literature review for Belitung public perception. There is a different awareness of people from East Belitung to the other areas. In East Belitung, knowledge of O. spilurus links to the local culture. Fishers have the most relevant fishing gear expertise for the catch of O. spilurus, based on environmental factors and fish behavior. Large-scale fishing, consumption, and trade only take place in East Belitung. It is impacted by non-environmentally sustainable mesh size nets that threaten their natural survival.